PENERAPAN NILAI-NILAI PENDIDIKAN ISLAM DALAM MEMBANGUN RELIGIUSITAS PESERTA DIDIK - Rendy Putra; Hafidz Hafidz (PAI RAFAH, 2023)
This study aims to determine the application of Islamic education values to students at MTs Negeri 1 Surakarta. The focus of discussion, namely: (1) The Implementation Process of Islamic Education Values at MTs Negeri 1 Surakarta. (2) The Role of Teachers and School Policies in the Implementation of Islamic Education Values at MTs Negeri 1 Surakarta. (3) Impact, Supporting Factors, and Obstacles in the Implementation of Islamic Education Values at MTs Negeri 1 Surakrta. This research uses a qualitative method with a descriptive approach. Data sources were taken from primary data and secondary data. The results of this study indicate that the process of implementing the values of Islamic education at MTs Negeri 1 Surakarta includes: (1) implementing the smile, greeting, and greeting program commonly referred to as 3S, (2) reading asmaul husna, (3) recitation of the Qur'an, (4) praying, (5) dhuha prayer, (6) dhuhur prayer and cultum, (7) commemoration of Islamic holidays (PHBI). The role of teachers and school policies as supervisors and rule makers. The application of Islamic education values has had an impact on students because it has become a habit. But in its implementation, there are certainly supporting factors and also inhibiting factors.